La prescripción de oficio de infracciones administrativas como extinción del IUS puniendi de la administración pública - Calderón Sare, Eder Rubén (2017)
The statute of limitations in administrative sanctioning procedures as regulated in Law Nº 27444, Law on General Administrative Procedure is clearly insufficient, consequently causing various complications at the time of its application. Thus, the central problem lies in whether this legal institution must declare ex officio by public entities or previously it needs a request from the intervening administration. This in light of the principle of administrative legality, generates the existence of two interpretations within the same public administration which are contradictory to each other. It is for this reason that we have analyzed the causes and consequences of the existence of this problematic interpretative of the norm, for which it has been taken into account that under the principle of legality, the public administration is obliged to comply with the Constitution and Laws, consequently that it is only allowed to perform that for which it is authorized in express norm. Thus, the administration must comply with the national legal system and can not exceed the authorized powers. Thus, we can observe that a group of institutions such as groups such as the National Water Authority (ANA) and the Environmental Monitoring Agency (OEFA), which, when examining their competence to open or continue a sanctioning procedure, verify that the prescription is operating by resolution Shall declare ex officio the limitation of their sanctioning power. However, another group, such as the Ministry of Education (MINEDU), the OSCE State Procurement Tribunal and others, despite having verified the deadlines for stating the limitation period, continue with the procedure for the interested party to allege By means of a defense in accordance with what is established in article 233 of the Law of General Administrative Procedure